2020
DOI: 10.22271/chemi.2020.v8.i2aj.9104
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of tomato (Lycopersicon esculentum Mill.), chilli (Capsicum annum L.), cucumber (Cucumis sativus L.) and Bhendi (Abelmoschus esculentus L.) for salinity stress

Abstract: Salinity is one of the most important abiotic stresses limiting yield potential. Salinity is even more harmful to seed germination and seedling development. The present study aimed to evaluate the effect of the salinity on germination and seedling growth in four different vegetable crops viz., tomato, chilli, cucumber and bhendi. In this study, germination percentage (%), shoot length (cm), root length (cm), root to shoot ratio, fresh and dry weight (g) were recorded at four different salinity levels (50 mM, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is well known that salt stress severely impacts crop production worldwide by reducing growth and yield [14,15]. Specifically, the growth parameters of different germplasms show significantly different responses to salt stress, such as the germplasms of cucumber, tomato, and chilli [6][7][8]. In asparagus, we also found that 95 germplasm accessions exhibited different salt tolerance with a large variation.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…It is well known that salt stress severely impacts crop production worldwide by reducing growth and yield [14,15]. Specifically, the growth parameters of different germplasms show significantly different responses to salt stress, such as the germplasms of cucumber, tomato, and chilli [6][7][8]. In asparagus, we also found that 95 germplasm accessions exhibited different salt tolerance with a large variation.…”
Section: Discussionmentioning
confidence: 56%
“…In recent years, considerable research on the identification of salt-tolerant germplasm has been carried out in multiple vegetables around the world, such as cucumber, tomato, and chilli [6][7][8], from which some success and experience have been achieved. However, in asparagus, the research is still in the initial stage and lacks depth and breadth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity negatively impresses plant growth by disturbing water balance, specific ion toxicity, creating an imbalance in plant nutrition, and combinations of these factors, and affecting plant physiological and biochemical processes (Loganayaki et al 2020). Ionic effects related to NaCl stress induce damages of macromolecules and compartments of the cells such as cell membrane, cell wall, lipits, proteins, and nucleic acids as a result of nutritional disorders in leaves and meristems (Aly et al 2012).…”
Section: Introductionmentioning
confidence: 99%